Role of Ferroptosis in Glial Cells after Ischemic Stroke - Shu-Ying Xu; Si-Ming Ni; Chun-Li Zeng; Yong-Jun Peng (Frontiers in Bioscience-Landmark, 2023)
Ischemic stroke (IS) is the predominant cause of morbidity and mortality worldwide. Ferroptosis, a new type of programmed cell death, has been shown to play a crucial role in IS pathogenesis. Traditionally, research focused on neurons did not uncover specific positive results for IS. However, glial cells have recently received interest as promising targets for IS treatment, not only for their structural function but also in the iron transfer between glia and neurons, which indicates a promising glia–neuron crosstalk in mediating the IS process and ischemia/reperfusion-associated neuropathology, showing their affiliation with ferroptosis. This review addresses the major phenomena of iron metabolism and the process and regulation of ferroptosis, with a particular focus on their impact on IS pathology. The review discusses iron homeostasis, the biology of reactive oxygen species, and lipid peroxidation for modulating the process of IS-induced ferroptosis in different glial cells. We then review recent therapies that leverage ferroptosis modulation for the treatment of IS. Extensive preclinical and clinical research is necessary to fully understand the roles of glia–neuron crosstalk and ferroptosis in IS.